Kekuatan Sosialisasi dalam Paradiplomasi Kedaulatan Bangsa Kurdi di Timur Tengah - Karisma, Gita; Nizar, Moh; Wiranata, Indra Jaya; Mumtaz, Sonya (LP3M Universitas Dharma Wacana, 2024)
While the trend of cooperation on the globalization era is rising, the cities involvement on the diplomatic activities is increasing. The central government also encourages the paradiplomacy considering the benefits that will return to its state. However, recently, paradiplomacy has also been carried out not only to pursue the economic interests and development aspects but also to fight for security, identity, and sovereignty aspect. Several cities and even autonomous regions have shown the ability to implement and develop their paradiplomacy. This article using qualitative approach to examine sovereign paradiplomacy of the Kurdistan Regional Government (KRG) which was established as an autonomy region within Iraq. The KRG has long demanded for independence and has even been able to expand its paradiplomacy to the Middle East and the world. The KRG's paradiplomacy is successful and strong enough which is can be seen when referendum was be held by KRG in 2017. The KRG has the power of socialization and shared the values ​​as a form of construction that the KRG has carried out for a long time on its paradiplomacy. The KRG has repeatedly stated that the KRG's paradiplomacy is constitutionally valid. Though, KRG always shows a cooperative attitude and expertise in diplomacy. He was even able to show the similarity of the values ​​of the Kurdish identity and the identity of anti-terorism and democracy as the basis for cooperation, even the values ​​that became the basis for the acceptance of Kurdish paradiplomacy by countries in the Middle East.